2018
DOI: 10.2147/idr.s152090
|View full text |Cite
|
Sign up to set email alerts
|

Durability, safety, and efficacy of rilpivirine in clinical practice: results from the SCOLTA Project

Abstract: Rilpivirine is associated with a good efficacy and safety profile. However, data from real-life settings are scarce.MethodsWe investigated the durability, safety and efficacy of Rilpivirine-based antiretroviral therapy in a prospective, observational, multicenter study.ResultsWe enrolled 499 HIV-infected patients, 360 (72.1%) males, mean age 43.4 ± 10.5 years, mean CD4 600 ± 327 cell/μL, mean HIV-RNA 3.80 ± 1.15 log10 cp/mL. After a median follow up of 16 months, 81 (16.2%) interruptions were reported, 36 (7.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
(35 reference statements)
3
14
0
1
Order By: Relevance
“…There were two participants who discontinued RPV due to hepatitis (Grade 2–3). This finding is consistent with other studies [19, 21].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…There were two participants who discontinued RPV due to hepatitis (Grade 2–3). This finding is consistent with other studies [19, 21].…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with other studies [14, 19, 20]. We observed a lower rate of RPV treatment discontinuation due to AE in our study compared to a previous study [21] (1.6% vs 7.2%).…”
Section: Discussionsupporting
confidence: 93%
“…[29] On the contrary, PI triple therapy might be more generally prescribed to anyone, but demonstrated lower durability [30, 31], mainly for simplification or tolerability issues. Indeed, PIs have now many competitors in the modern ART scenario, including integrase inhibitors and rilpivirine, characterized by good tolerability and high durability [3235]. In fact, despite DRV/c can be used in both naïve and experienced patients, our results showed as, in real life, it was mainly used in subjects switching from antiretroviral treatments already containing PI.…”
Section: Discussionmentioning
confidence: 86%
“…These results were higher than in other published observational studies reporting discontinuation rates of 13-16% in TEP but with shorter follow-up of 12-16 months. 17,18 In contrast, Sculier et al reported 25% of discontinuation after a median time of 18.4 months. 22 Finally, our result was lower than the 34% showed by Bernaud et al, where the median time of follow-up was similar (36 months).…”
Section: Discussionmentioning
confidence: 96%
“…16 However, studies combining PK and efficacy of RPV are lacking in real-life contexts. [17][18][19][20][21][22] Hence, the present study assessed the antiviral activity of the RPV/FTC/TDF regimen and described the association of RPV exposure with virologic response and resistance in a cohort of NP and treatment-experienced patients (TEP) over 3 years of follow-up. What is known about this subject…”
mentioning
confidence: 99%